The social theory of the business model of Huawei and its implementation - L. V. Filindash (Вестник университета)
The social component of the personnel policy of Huawei Technologies is considered. As the largest international, multinational telecommunications corporation, Huawei successfully solves the problem of forming corporate unity. The directions of its effective social strategy are of scientific and practical interest. In the article, based on official data on the personnel structure, it is revealed that the principle of personality psychotypes is used in the practice of creating a stable structure, which determines the novelty of the material. One of the directions of this research is to clarify the special social rhetoric used in verbal and nonverbal communication. Since Huawei has many educational centers on the territory of Russia based on domestic universities, the authors of the article see their task to acquaint today’s students – potential employees of the company with the social policy of their future employers.